Pengaruh Dewan Komisaris Independen, Kepemilikan Manajerial, dan Kepemilikan Institusional terhadap Kinerja Keuangan - Imaniyyah, Amanatul; Muthaher, Osmad (CV. ITTC INDONESIA, 2025)
This research is motivated by the importance of financial performance as an indicator of a company's effectiveness in managing resources, especially amidst global and national economic uncertainty. The slowdown in global economic growth and declining purchasing power have impacted the stability of company performance, making strengthening governance crucial. The emerging issue is the role of the Independent Board of Commissioners, Managerial Ownership, and Institutional Ownership in improving the financial performance of primary consumer goods manufacturing companies in Indonesia. The purpose of this study is to analyze the influence of these three factors on financial performance. The study used a quantitative approach with a purposive sampling method. The research sample consisted of 59 companies that met the criteria with a total of 177 observation data for the period 2021–2023. Data were obtained from the annual reports of companies listed on the Indonesia Stock Exchange and analyzed using multiple linear regression using SPSS. The results show that the Independent Board of Commissioners and Institutional Ownership have a significant positive effect on financial performance, while Managerial Ownership has a negative but insignificant effect. These findings underscore the importance of independent parties and institutional investors in strengthening oversight, while high levels of managerial ownership require vigilance to prevent conflicts of interest. This research contributes to the literature on good corporate governance and offers practical implications for companies in improving financial performance amid economic uncertainty.